Amifostine Analog, DRDE-30, Attenuates Bleomycin-Induced Pulmonary Fibrosis in Mice - Arora, Aastha; Bhuria, Vikas; Hazari, Puja P.; Pathak, Uma; Mathur, Sweta; Roy, Bal G.; Sandhir, Rajat; Soni, Ravi; Dwarakanath, Bilikere S.; Bhatt, Anant N. (Frontiers in Pharmacology, 2018)
Bleomycin (BLM) is an effective curative option in the management of several malignancies including pleural effusions; but pulmonary toxicity, comprising of pneumonitis and fibrosis, poses challenge in its use as a front-line chemotherapeutic. Although Amifostine has been found to protect lungs from the toxic effects of radiation and bleomycin, its application is limited due to associated toxicity and unfavorable route of administration. Therefore, there is a need for selective, potent, and safe anti-fibrotic drugs. The current study was undertaken to assess the protective effects of DRDE-30, an analogue of Amifostine, on bleomycin-induced lung injury in C57BL/6 mice. Whole body micro- computed tomography (CT) was used to non-invasively observe tissue damage, while broncheo- alveolar lavage fluid (BALF) and lung tissues were assessed for oxidative damage, inflammation and fibrosis. Changes in the lung density revealed by micro-CT suggested protection against bleomycin- induced lung injury by DRDE-30, which correlated well with changes in lung morphology and histopathology. DRDE-30 significantly blunted bleomycin-induced oxidative stress, inflammation and fibrosis in the lungs evidenced by reduced oxidative damage, endothelial barrier dysfunction, Myeloperoxidase (MPO) activity, pro- inflammatory cytokine release and protection of tissue architecture, that could be linked to enhanced anti-oxidant defence system and suppression of redox-sensitive pro- inflammatory signalling cascades. DRDE-30 decreased the bleomycin-induced augmentation in BALF TGF-β and lung hydroxyproline levels, as well as reduced the expression of the mesenchymal marker α- smooth muscle actin (α- SMA), suggesting the suppression of epithelial to mesenchymal transition (EMT) as one of its anti- fibrotic effects. The results demonstrate that the Amifostine analogue, DRDE-30, ameliorates the oxidative injury and lung fibrosis induced by bleomycin and strengthen its potential use as an adjuvant in alleviating the side effects of bleomycin.